Rural development in the era of globalization in Bangladesh - Ferdous, Jannatul (Public administration) (Economic issues, problems and perspectives, 2021)
"Rural Development is a deliberate transformation towards the advancement of the financial and societal standard of living of the rural poor through amplified production, impartial delivery of possessions, and empowerment. In general, a deliberate transformation towards rural institution building and progression in technology. Bangladesh, nearly 50 years into its liberation, stays on the route to development and the country is looking forward to transitioning into a developed state by 2041. There is global pressure also. Rural development plays a key role in attaining the targets. The Bangladesh Academy for Rural Development (BARD) is a pioneer institute for attaining rural development in Bangladesh. The academy is acknowledged as a center of excellence regarding training, research and action research. The institute was established in 1959 with the intention of provide training to the public officials and representatives of the local government and village institutions on diverse matters concerning to rural development. Still, the institution provides training to diverse stakeholders. Moreover, a large quantity of international clientele comprising scholars, research fellows, experts, government bureaucrats, affiliates of diplomatic corps and global organizations visit the academy. The academy has been steering socio-economic study from the time of its beginning. Research outcomes are used as training resources and contributions for introducing action research by the Academy itself. It also works as data resources and policy ideas for the policy makers, Ministries, and Planning Commission. In certain circumstances, these are also dispersed among the global organizations and institutes. BARD conducts investigational projects to progress models of better-quality institution, managerial arrangements in addition to harmonization and approaches of production. The project events generally include the villagers' development institutes, local bodies and public officials. To this point the Academy has directed more than 50 investigational projects on different facets of rural development. Finally, in the era of globalization and pressure of implementation of Sustainable Development Goals (SDGs), the book provides an immense knowledge on "Rural Development" issue in Bangladesh perspective"--